Impact of Sarcopenia on Adverse Outcomes After Allogeneic Hematopoietic Cell Transplantation. (14th February 2019) - Armenian, Saro H; Xiao, Meisi; Berano Teh, Jennifer; Lee, Brandyn; Chang, Howard A; Mascarenhas, Kristen; Lee, Sean; Iukuridze, Alex; Xie, Jack J; Scott, Jessica M; Jones, Lee W; Lennie Wong, F; et al.
Abstract: Background: High intensity treatments such as hematopoietic cell transplantation (HCT) can be curative for patients with hematologic malignancies, but this needs to be balanced by the high risk of nonrelapse mortality (NRM) during the first 2 years after HCT. Sarcopenia (low muscle mass) is associated with physical disability and premature mortality in individuals with nonmalignant diseases and may be a predictor of NRM and poor overall survival in patients undergoing HCT. Methods: This was a retrospective cohort study of 859 patients with acute leukemia or myelodysplastic syndrome who underwent a first HCT as adults (≥18 years) between 2007 and 2014. Sarcopenia was assessed from pre-HCT abdominal computed tomography scans. Two-year cumulative incidence of NRM was calculated, with relapse/progression considered as a competing risk event. Fine-Gray subdistribution hazard ratio estimates and 95% confidence intervals (CI) were obtained and adjusted for relevant covariates. Kaplan-Meier method was used to examine overall survival. All statistical tests were two-sided. Results: Median age at HCT was 51 years (range = 18–74 years); 52.5% had a high [≥3] HCT-comorbidity index; 33.7% had sarcopenia pre-HCT. Sarcopenia was an independent predictor of higher NRM risk (hazard ratio = 1.58, 95% CI = 1.16 to 2.16) compared with patients who were not. The 2-year incidence of NRM approached 30% in patients with sarcopenia and high (≥3) HCT-comorbidity index. Patients with sarcopenia had on average a longer hospitalization (37.2 days vs 31.5 days, P  < .001) and inferior overall survival at 2 years (55.2%, 95% CI = 49.5% to 61.0% vs 66.9%, 95% CI = 63.0% to 70.8%, P  < .001). Conclusions: Sarcopenia is an important and independent predictor of survival after HCT, with potential additional downstream impacts on health-economic outcomes. This information can be used to facilitate treatment decisions prior to HCT and guide interventions to decrease the risk of treatment-related complications after HCT.